Effect Trichoderma spp on wheat (Triticum aestivum) - Aljboori, Qasim H. A.; Babenko, Andrey S.; Gulik, Elena S.; Kurovsky, Alexander V.; Mikhaylova, Svetlana I. (IOP Conference Series: Earth and Environmental Science)
The objective this study were to determine effect of Trichoderma spp and Humic acid 60% on three Varieties of wheat (Triticum aestivum). The study included two factors،first factor was immersion of seeds in Humic acid 60% solution Humic acid 60% + Trichoderma spp150Mg/l ،Humic acid 60% + Trichoderma spp 250Mg/l،symbols T1 ،T2، T3،T4 respectively. The second factor is three varieties of wheat (Iba99 ،Adina ،Dijlla) and the plant variety is represented by V1 ،V2،V3 respectively. Treatments were Design (RCBD) with three replicates Statistics were evaluated followed by Duncan multiple range test to compare means at P<(0.05). Data presented the use of Humic acid 60% + Trichoderma spp250 Mg/l led to a significant increase in the studied traits as well as the interaction between variables where treatment V2T4 were highest significant increase in plant height، root length and spike length ، which reached 95.07 cm plant height ،14.93 cm length Root ،spike length is 11.50 cm ،while treatment V1T4 were the highest significant increase in leaf reach ،reaching 26.80 cm.